Strategy Analysis of ZIS Fund Collection During the Covid-19 Pandemic at Baznas DKI Jakarta Province - Dafiq, Muhammad Ilman; Rohim, Ade Nur; Priyatno, Prima Dwi (El-Barka Journal of Islamic Economics and Business, 2021)
During the Covid-19 pandemic, Muslims in Indonesia have high awareness to help each other on religious social matters, such as Zakat, Infaq, and Shadaqah (ZIS). Covid-19 pandemic requires ZIS gathering institutions in Indonesia such as Baznas to innovate in conducting service activities to the community, especially ZIS gathering. This needs to be done to facilitate community and reduce the risk of spreading the virus through crowding activities. Suitable strategy is required in order for ZIS can collection services to continue to run even with limited conditions. The purpose of this study is to analyze the strategy carried out by Baznas DKI Jakarta Province in collecting ZIS during Covid-19 Pandemic and analyze the supporting factors and inhibitory factors of the implementation of the strategy carried out by the Baznas DKI Jakarta Province. The method used in this study is descriptive qualitative using SWOT analysis. The study used primary data through interviews. As well as secondary data through observation and documentation of previous research, company profile, and books. The results of the study showed Baznas DKI Jakarta Province has supporting factors and inhibitory factors, among others related to the digitization of ZIS, government policies, and awareness of carrying out ZIS payments.